Daya Antibakteri Ekstrak Metanol Buah Okra (Abelmoschus esculentus (L.) Moench) - puah, Siti Mar; Astuti, Winni; Hindryawati, Noor (Jurusan Kimia FMIPA UNMUL, 2021)
ABSTRACT Phytochemical test and antibacterial activity of methanol extract of Okra (Abelmoschus esculentus (L.) Moench) fruit have been carried out. Extraction using maceration method. The methanol extract of Okra fruit contains phenolic secondary metabolites, alkaloids and steroids. Antibacterial activity opposes the agar diffusion method against the bacteria Salmonella typhi and Steprococcus mutans. The Minimum Inhibitory Concentration Value of Okra fruit methanol extract against Salmonella typhi bacteria at a concentration of 0.625-1.25% and against Streptococcus mutans bacteria 1.25% -2.5%. Okra fruit methanol extract has antibacterial activity with wide variations. Keywords : Abelmoschus esculentus (L.) Moench, antibacterial activity, secondary metabolites, Minimum Inhibitory Concentration (MIC).